1981
DOI: 10.1007/bf01561689
|View full text |Cite
|
Sign up to set email alerts
|

The location ofC2, C4, andBF relative toHLA-B andHLA-D

Abstract: The loci for HLA-A,B,C,D, and DR are known to be closely linked to the structural loci for the complement components C2, BF, and the duplicated loci for C4, C4A and C4B. Conflicting evidence has been presented for the order of these genes. However, new techniques have made possible identification of markers in the HLA-D and C4 region for nearly all identified haplotypes. In our population we have confirmed five HLA-B-D crossovers and in each case informative allotypes of C2, BF, or C4A and C4B segregated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The four gene complement haplotypes are inherited as single genetic units which are called complotypes. We previously identified 14 common and distinct complotypes in normal Caucasians (12) and showed that they are closely linked to HLA-DR (13). HLA-B, DR, and complotype combinations with significant linkage disequilibrium among normal chromosomes were defined as extended haplotypes (14).…”
Section: Introductionmentioning
confidence: 99%
“…The four gene complement haplotypes are inherited as single genetic units which are called complotypes. We previously identified 14 common and distinct complotypes in normal Caucasians (12) and showed that they are closely linked to HLA-DR (13). HLA-B, DR, and complotype combinations with significant linkage disequilibrium among normal chromosomes were defined as extended haplotypes (14).…”
Section: Introductionmentioning
confidence: 99%
“…No crossover has yet been observed between C2*QO and BF (24) or C2 and BF (10). Finally, the loci for C2, BF, C4A, and C4B are thought to be close to HLA-D and HLA-DR with no observed recombination between them (25).…”
Section: Introductionmentioning
confidence: 99%
“…They are also very close to HLA-D, DR (4), perhaps located between HLA-D, DR and HLA-B. In family studies involving a large number of informative meioses, no crossovers among the serum complement loci were detected, suggesting that specific BF, C2, C4A, and C4B alleles form haplotypes (complotypes) that are inherited as gametic units.…”
mentioning
confidence: 97%